2021
DOI: 10.1039/d1lc00048a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a human neuromuscular tissue-on-a-chip model on a 24-well-plate-format compartmentalized microfluidic device

Abstract: Engineered three-dimensional models of neuromuscular tissues are promising for use in mimicking their disorder states in vitro. Although several models have been developed, it is still challenging to mimic the...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Other authors have reported functionality of in vitro NMJs from different cell sources [ 107 , 108 , 109 ]. This was done by evaluating muscle contraction upon excitation of MN, either by glutamate [ 110 , 111 ] or optogenetic [ 112 , 113 ] or electrophysiological [ 108 , 114 ] stimulation and by testing the specificity of transmission response by antagonists which either blocked ACh release or binding [ 16 , 107 , 115 ]. In this context, it would be informative to integrate hiPSC-derived SC into NMJ culture systems suited for such readouts in order to evaluate a possible impact on in vitro NMJ functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported functionality of in vitro NMJs from different cell sources [ 107 , 108 , 109 ]. This was done by evaluating muscle contraction upon excitation of MN, either by glutamate [ 110 , 111 ] or optogenetic [ 112 , 113 ] or electrophysiological [ 108 , 114 ] stimulation and by testing the specificity of transmission response by antagonists which either blocked ACh release or binding [ 16 , 107 , 115 ]. In this context, it would be informative to integrate hiPSC-derived SC into NMJ culture systems suited for such readouts in order to evaluate a possible impact on in vitro NMJ functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Human iPSC clones (201B7 [ 17 ]) provided by Dr. Shinya Yamanaka (RIKEN BRC through the Project for Realization of Regenerative Medicine and National Bio-Resource Project of the MEXT, Japan) were cultured and differentiated into MNs, as reported previously [ 18 , 19 ]. Some hiPSC-derived MN spheroids cultured for 14 or 15 days were collected in a 15 mL tube and washed twice with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…[ 431 ] Finally, microdevices with separate chambers for the precise compartmentalization of motoneurons and skeletal muscle tissues, which fit the well size of 24 well plates, have been proposed tools for fundamental research and drug development for neuromuscular disorders (Figure 13I). [ 432 ]…”
Section: Microfluidics For Bio‐actuatorsmentioning
confidence: 99%
“…[431] Finally, microdevices with separate chambers for the precise compartmentalization of motoneurons and skeletal muscle tissues, which fit the well size of 24 well plates, have been proposed tools for fundamental research and drug development for neuromuscular disorders (Figure 13I). [432] Of note, microfluidic platforms for neuromuscular junction modeling can also include optically excitable cells. Uzel et al differentiated motor neurons from mouse embryonic stem cells and co-cultured them with myoblast-derived muscle strips within a 3D hydrogel (Figure 14).…”
Section: Functional Control Of Muscle Tissue In Microfluidic Devicesmentioning
confidence: 99%